Effect of ectomycorrhizal inoculum produced by solid state fermentation on growth of Eucalyptus dunnii Maiden - Alves, João Rogério; Souza, Ozair de; Podlech, Pablo Angel Sanchez; Giachini, Admir José; Oliveira, Vetúria Lopes de (Pesquisa Agropecuaria Brasileira, 2001)
Growth of Eucalyptus can be improved by ectomycorrhizal fungi (ECMF). Although widespread in forest plantations, ECMF differ in infectivity and effectiveness, hence the need of selection of compatible and efficient ECMF and the establishment of inoculum production methods. The objective of this study was to test compatibility and efficiency of the ectomycorrizal inoculum produced by solid state fermentation, in relation to Eucalyptus dunnii Maiden. For this purpose, inoculum of Pisolithus sp. was produced by solid state fermentation in vermiculite + nutrient solution and applied to peat:vermiculite (30:70 v/v) at 0, 1, 3, 5 and 10% (v/v). Seeds of E. dunnii were sown and kept in a glasshouse. Inoculation promoted root colonization, plant growth and phosphorus (P) uptake depending upon inoculum concentration. Plant dry matter with 1% inoculum did not differ from that of the controls. At 3% and 5%, plants had 60% more dry matter than the controls. At 10%, inoculum shoot dry weight (dw) was 70% higher, and P content was 130% higher than that of the controls. Similar results were obtained in relation to root dw. Height and diameter were also positively affected by inoculation. Root:shoot ratios were not influenced. The most efficient doses were those at 3% inoculum or higher. This method of inoculum production needs to be tested with other ECMF and its efficiency must be evaluated in the nursery and in the field.